Numerical simulations of heavily polluted fine-grained sediment remobilization using 1D, 1D+, and 2D channel schematization - Kaiglová, Jana; Langhammer, Jakub; Jiřinec, Petr; Janský, Bohumír; Chalupová, Dagmar (Environmental monitoring and assessment, 2015)
This article used various hydrodynamic and sediment transport models to analyze the potential and the limits of different channel schematizations. The main aim was to select and evaluate the most suitable simulation method for fine-grained sediment remobilization assessment. Three types of channel schematization were selected to study the flow potential for remobilizing fine-grained sediment in artificially modified channels. Schematization with a 1D cross-sectional horizontal plan, a 1D+ approach, splitting the riverbed into different functional zones, and full 2D mesh, adopted in MIKE by the DHI modeling suite, was applied to the study. For the case study, a 55-km stretch of the Bílina River, in the Czech Republic, Central Europe, which has been heavily polluted by the chemical and coal mining industry since the mid-twentieth century, was selected. Long-term exposure to direct emissions of toxic pollutants including heavy metals and persistent organic pollutants (POPs) resulted in deposits of pollutants in fine-grained sediments in the riverbed. Simulations, based on three hydrodynamic model schematizations, proved that for events not exceeding the extent of the riverbed profile, the 1D schematization can provide comparable results to a 2D model. The 1D+ schematization can improve accuracy while keeping the benefits of high-speed simulation and low requirements of input DEM data, but the method's suitability is limited by the channel properties.
Keywords: znečištění životního prostředí; geologické sedimenty; monitorování životního prostředí; Evropa; Environmental Monitoring; Environmental Pollution; Metals, Heavy; chemické modely; Cross-Sectional Studies; Models, Chemical; Geologic Sediments; látky znečišťující vodu; průřezové studie; řeky; Rivers; Europe; Water Pollutants; těžké kovy